Utilizing Text-to-Speech (TTS) Technology in Creating Listening Materials for English Language Teaching (ELT) - Fitria, Tira Nur (Journal of English Language and Culture, 2024)
This research stimulates the use of Text-to-Speech (iSpeech) in creating English listening materials. The analysis shows that in using iSpeech Text-to-Speech, click the web https://www.ispeech.org/text.to.speech. Enter sentences or texts in the text box provided. Choose a male or female voice and choose the accent language we want to use to convert text to audio including UK (British) or US (American) English. To start the process synthesize sentences or text, press the Play button, and text that is currently sounded will be automatically blocked in yellow. Download the audio output and the audio can be played to students as listening materials in teaching English. Save the results of the synthesis into audio form in a certain format, so it can be heard again wherever and whenever by our students. With the presence of speech synthesizer technology, of Text-To-Speech (TTS) system can perform conversions from text computer-generated in the form of pronunciation (audio), where audio the resulting speed can be adjusted, intonation (prosody), as well as audio format output to be saved in the form of an audio file. English teachers/ lecturers can create listening materials according to their needs which will be taught to students.